Gauchism and the schools: cultural diversity in question - Ceres Karam Brum (Universidade Federal do Rio Grande do Sul, 2013)
In this text we wish to perform a reflection about Gauchism and Traditionalism in Rio Grande do Sul. We start from the mythical construction of the gaucho figure and its uses by Gauchism, which identifies this figure as the ideal pattern to be internalized by multiple learning processes. As a conclusion, we want to highlight some dimensions of the discourse of cultural diversity in contexts such as the cult of Gauchism and of the Traditionalism nowadays. We are based on a bibliographic analysis and fieldwork which demonstrate the educational scenery as a field of disputed permeated by different forms of symbolic violence, which involves ideas, values and imaginaries in the processes of construction of regional identities.